Amar Ma’ruf Nahi Munkar Dalam Persfektif Syekh Abdussomad al-Palimbani dalam Kitabnya Sairussalikin Ila Ibadah Robbal ‘Alamin: Relevansinya Dengan Aktifitas Dakwah - Choiriyah Choiriyah (Wardah, 2019)
Abstrak One of Ulama Nusantara's works, Sheikh Abdussomad al-Palimbani, which until now continues to receive attention from academics, is a book called Sairussalikin Ila Ibadah Robbal ‘Alamin. This monumental work describes aspects of the creed, fiqh and Sufism, and the study of Sufism seems to be more dominant than other aspects. Interestingly in the second volume the Author also explained about the concept of amar ma'ruf nahi munkar. This paper will explain Sheikh Abdussomad al-Palimbani's thoughts about amar ma'ruf nahi munkar: Its relevance to the implementation of da'wah. Abdussomad al-Palimbani believes that in amar ma'ruf nahi munkar there must be al-muhtasib, al-muhtasib alayhi, al-muhtasib fihi, and nafs ihtisab. Abdussomad al-Palimbani's thoughts can be applied in the implementation of da'wah at this time, especially on the issue of preaching targets which must also be oriented to the authorities or officials. Kata Kunci : Amar ma’ruf , Nahi Munkar, Relevansi , Aktifitas dakwah